2013
DOI: 10.1186/2040-2392-4-39
|View full text |Cite
|
Sign up to set email alerts
|

Differential recruitment of coregulators to the RORA promoter adds another layer of complexity to gene (dys) regulation by sex hormones in autism

Abstract: BackgroundOur independent cohort studies have consistently shown the reduction of the nuclear receptor RORA (retinoic acid-related orphan receptor-alpha) in lymphoblasts as well as in brain tissues from individuals with autism spectrum disorder (ASD). Moreover, we have found that RORA regulates the gene for aromatase, which converts androgen to estrogen, and that male and female hormones regulate RORA in opposite directions, with androgen suppressing RORA, suggesting that the sexually dimorphic regulation of R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
54
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 55 publications
(56 citation statements)
references
References 68 publications
2
54
0
Order By: Relevance
“…Regardless of sex differences, the underlying mechanisms driving regional and developmental differences in RORA expression, such as those seen in the OFC, are unclear. Recently, we described differential recruitment of co-regulator proteins that are involved in the sex hormone-dependent regulation of RORA in the SH-SY5Y neuronal cell model [ 41 ]. We demonstrated that estrogen-mediated upregulation of RORA expression required both the estrogen receptor (ER-alpha) and the coactivator NCOA5, while androgen (DHT)-mediated downregulation of RORA required the androgen receptor (AR) and the corepressor function of SUMO1.…”
Section: Discussionmentioning
confidence: 99%
“…Regardless of sex differences, the underlying mechanisms driving regional and developmental differences in RORA expression, such as those seen in the OFC, are unclear. Recently, we described differential recruitment of co-regulator proteins that are involved in the sex hormone-dependent regulation of RORA in the SH-SY5Y neuronal cell model [ 41 ]. We demonstrated that estrogen-mediated upregulation of RORA expression required both the estrogen receptor (ER-alpha) and the coactivator NCOA5, while androgen (DHT)-mediated downregulation of RORA required the androgen receptor (AR) and the corepressor function of SUMO1.…”
Section: Discussionmentioning
confidence: 99%
“…[ 29 ] look into specific sex-implicated aetiological mechanisms. Their previous studies show that autism may be associated with deficiency in the expression of the retinoic acid-related orphan receptor alpha (RORA) gene, and therefore, dysregulated feedback loops with androgen and oestrogen, as well as the many autism-associated genes regulated by RORA [ 62 , 23 , 22 ]. In their new article, Hu et al .…”
Section: Editorialmentioning
confidence: 99%
“…For instance, androgens and estrogens differentially regulate the RORA gene, a candidate susceptibility gene for autism, the expression of which is low in the frontal cortex of autistic individuals [ 171 ]. The product of this gene, which promotes the conversion of T into estrogen, also acts through co-activators, demonstrating the complexity of the gene/hormone interactions [ 172 ].…”
Section: Reviewmentioning
confidence: 99%